The trouble in me [compact disc, unabridged] - Gantos, Jack (Macmillan Audio, 2015)
A pivotal week or two in the life of fourteen-year-old Jack Gantos, as the author reveals the moment he began to slide off track as a kid who in just a few years would find himself locked up in a federal penitentiary.